Surgical excision versus imiquimod 5% cream for nodular and superficial basal-cell carcinoma (SINS): a multicentre, non-inferiority, randomised controlled trial - Bath-Hextall, Fiona; Ozolins, Mara; Armstrong, Sarah J.; Colver, Graham B.; Perkins, William; Miller, Paul S.J.; Williams, Hywel C. (Elsevier, 2014)
Background Basal-cell carcinoma is the most common form of skin cancer and its incidence is increasing worldwide. We aimed to assess the effectiveness of imiquimod cream versus surgical excision in patients with low-risk basal-cell carcinoma.